Pengaruh Penggunaan Media Pembelajaran Quizlet dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas V SDN Sayabulu - Estiana Parlina; Ajo Sutarjo; Muhammad Hanif (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The purpose of this study is to find out that learning activities with the help of Quizlet can affect the ability of fifth grade students at SDN Sayabulu, especially in critical thinking skills. Before conducting the research, the researcher interviewed the homeroom teacher and one of the fifth grade students of SDN Sayabulu that the learning process rarely uses technology, teachers more often teach using conventional methods with the help of book media. Students' interest in learning can be reduced because one of the media is less varied so that it affects the development of students' critical thinking. From the results of these observations and interviews, researchers used an alternative learning media, namely Quizlet in learning activities in order to require students to think critically. Quizlet itself consists of several interesting features that can help students in learning, features such as flashcards, tests, and writing which emphasizes that students understand, analyze, identify, and provide answers to challenging questions or questions that require analysis and evaluation.learning Quizlet is expected to be a way out in improving the critical thinking skills of SDN Sayabulu students. The research was conducted at SDN Sayabulu which is located on Jl. Sayabulu, Serang City, Banten Province, with the research time in May 2022. The study population consisted of 42 fifth grade students at SDN Sayabulu, of which 38 students were sampled using probability sampling calculations. The researcher uses a quantitative method, namely the form of a one group pre-test post-test which includes the type of pre-experimental design to compare critical thinking of the fifth grade students of SDN Sayabulu before and after treatment with the Quizlet contained in one group or class. The results of the study using Quizlet for learning media, showed a significant increase, it was in the calculation of the parametric test by using the paired sample t test with the results of the sig.2 tailed value of 0.000 < 0.05, meaning that Ha learning media was accepted, then the influence of Quizlet in improve critical thinking of fifth grade students at SDN Sayabulu.